University Cities in Europe: Concept, Development Specifics and Urban Planning Patterns - D. P. Shatilo (Контуры глобальных трансформаций: политика, экономика, право, 2021)
The paper includes the analyses of university cities role in Europe, their properties and their origin causes. The main purpose of the article is the European university cities characteristics determination. The author clarified a concept of university city, since there is no clear scientific definition because each country has its own understanding of the university city meaning. In a narrow sense a university city is, as a rule, a small or medium-sized city, where the main socio-economic processes are closely related to the university and scientific activities. The general characteristics for a classifying a city as a university city is the historical and economic universities role and the total number of students and scientific workers. In Europe, most university cities are formed due to the long history. In medium and small university cities, the scientific and university cluster plays a city-forming role. Usually in older university cities, the university and campus occupy a vast area.In the research, the author analyzes specific examples of university cities. Attention is also paid to urban planning aspects because universities occupy vast city’s territory. Now in a knowledge-based society, universities play an important role including the linkages between the local and global levels of the knowledge economy. The city and university interaction is shown on the example of German university cities: Heidelberg, Göttingen, Marburg and Tübingen. It has been found that a young population structure is observed in these German cities. There is also a large proportion of young people among immigrants and residents with a migratory background.